Roof Configurations, Room Quality Parameters and Musical Performances: An Analysis of the São Paulo Hall. Issue 1 (March 2013) - Tenenbaum, Roberto A.; Oliveira, Lenine V.; Muller, Swen
The São Paulo Hall (SPH) is recognized by musicians and musical critics in general by its good acoustical quality. Having geometric dimensions similar to the ones of some famous concert halls, it has as an important feature a variable acoustics due to its movable roof, which is employed by musicians to tune the room according to the musical style, in an ad hoc procedure. This work addresses the acoustical quality of the São Paulo Hall and the dependence of its acoustics on the roof configuration. Impulse responses for one source, eight microphone and two dummy head positions, using the sweep-sine technique with pre-emphasis, were obtained for seven distinct roof configurations. Several details of the measurement procedures to ensure good accuracy and repetitiveness are widely discussed. The measurement results were then used to compute the main room acoustical quality parameters, for each octave band between 63 Hz and 8 kHz. The spatial average and deviation of these data are presented as a function of the frequency band. The influence of the roof configurations on the obtained acoustical parameters is then presented and discussed. Furthermore, comparative plots among some acoustical parameters presented by São Paulo Hall at the chosen roof configurations and two famous and representative halls from the classical and romantic periods are reported. It is concluded that the movable roof is very effective in modifying the room acoustics and that the musician's ad hoc choices seems to be quite good.